Copper-induced production of copper-binding supernatant proteins by the marine bacterium Vibrio alginolyticus. - Harwood-Sears, V (1990)
Growth of the marine bacterium Vibrio alginolyticus is temporarily inhibited by micromolar levels of copper. During the copper-induced lag phase, supernatant compounds which complex and detoxify copper are produced. In this study two copper-inducible supernatant proteins having molecular masses of ca. 21 and 19 kilodaltons (CuBP1 and CuBP2) were identified; these proteins were, respectively, 25 and 46 times amplified in supernatants of copper-challenged cultures compared with controls. Experiments in which chloramphenicol was added to cultures indicated that there was de novo synthesis of these proteins in response to copper. When supernatants were separated by gel permeation chromatography, CuBP1 and CuBP2 coeluted with a copper-induced peak in copper-binding activity. CuBP1 and CuBP2 from whole supernatants were concentrated and partially purified by using a copper-charged immobilized metal ion affinity chromatography column, confirming the affinity of these proteins for copper. A comparison of cell pellets and supernatants demonstrated that CuBP1 was more concentrated in supernatants than in cells. Our data are consistent with a model for a novel mechanism of copper detoxification in which excretion of copper-binding protein is induced by copper.